(untitled) (Dhaka University Journal of Science, 2024)
The primary goal of this study was to determine the presence of potassium bromate in bread samples both qualitatively and quantitatively, as well as to investigate the composition of the bread (moisture, ash, and sugar contents). Thirty different commercial bread samples from different areas of Dhaka city were collected for analysis. The ultraviolet-visible spectrophotometric technique was employed in this study to estimate potassium bromate in bread samples. It was based on the redox interaction of bromate and promethazine hydrocloride in an acidic medium which generate a red-pink coloration with maximum absorbance at 515nm. The amount of potassium bromate was found in the range of 1.24 to 24.91µg/g. Moisture and ash content were found to be 15.37 to 29.8% and 1.75 to 2.94%, respectively. The total sugar content was determined by the ultraviolet-visible spectrophotometric method by the modified phenol-sulfuric acid test and the maximum absorbance was obtained at 489 nm. Total sugar content was found in different types of white bread samples ranging from 3.33 to 11.31g per 100g. The average recovery (n=5) of potassium bromate was 91.58 ± 5.61% at a dosage of 10 μg/mL. Dhaka Univ. J. Sci. 72(1): 1-6, 2024 (January)